2021
DOI: 10.1080/13696998.2021.1915600
|View full text |Cite
|
Sign up to set email alerts
|

Novel acute therapies in the treatment of migraine: impact of re-dosing on cost–utility outcomes

Abstract: Recently, several novel therapies have been developed for acute treatment of migraine, all of which have shown considerable efficacy benefits over placebo. 1 Novel therapies include the calcitonin gene-related peptide (CGRP) receptor antagonists rimegepant (NURTEC ODT, Biohaven) 2 and ubrogepant (UBRELVY, Allergan) 3,4 and the 5HT-receptor agonist lasmiditan (REYVOW, Eli Lilly). 5 The design of pivotal trials for these therapies include a key difference, in that the rimegpant Phase III program only allowed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Additionally, the ICER review did not consider tablet burden, which is particularly relevant given that rimegepant studies only allowed a single dose, while repeat dosing of triptans and other novel acute agents may be needed to achieve a sustained benefit [ 47 – 49 ]. A recent analysis confirmed that when the re-dosing of ubrogepant and lasmiditan was taken into account, rimegepant was associated with lower cost per QALY gained than these other novel agents [ 50 ].…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, the ICER review did not consider tablet burden, which is particularly relevant given that rimegepant studies only allowed a single dose, while repeat dosing of triptans and other novel acute agents may be needed to achieve a sustained benefit [ 47 – 49 ]. A recent analysis confirmed that when the re-dosing of ubrogepant and lasmiditan was taken into account, rimegepant was associated with lower cost per QALY gained than these other novel agents [ 50 ].…”
Section: Discussionmentioning
confidence: 98%
“…An observational study using IBM® MarketScan® Early View commercial database looking at adults with a claim for lasmiditan, rimegepant or ubrogepant between 1 January 2020 and 31 August 2020 (58). Patients prescribed lasmiditan were more likely to have a history of insufficient response to a prior acute therapy compared to patients prescribed a gepant (50% vs. 40%; p < 0.05) (58). The main reason to change acute therapy was efficacy concern such as persistent or worsening migraine attacks, prolonged time to return to function, lack of two-hour pain freedom (58).…”
Section: Discussionmentioning
confidence: 99%
“…Patients prescribed lasmiditan were more likely to have a history of insufficient response to a prior acute therapy compared to patients prescribed a gepant (50% vs. 40%; p < 0.05) (58). The main reason to change acute therapy was efficacy concern such as persistent or worsening migraine attacks, prolonged time to return to function, lack of two-hour pain freedom (58). So many factors play a role in prescription decision such as the medication mechanism of action (lasmiditan: 47%, ubrogepant: 45%, rimegepant: 51%), physician comfort/familiarity (lasmiditan: 46%, ubrogepant: 49% vs rimegepant: 39%; p < 0.05), expectations of two-hour pain freedom (rimegepant: 48% vs. ubrogepant: 36%, lasmiditan: 32%; p < 0.05), expected time for return to normal function (rimegepant: 47% vs. ubrogepant: 38%, lasmiditan: 37%; p < 0.05), expected low need for redosing/use of rescue medications (rimegepant: 23% vs. ubrogepant: 14%, lasmiditan: 14%; p < 0.05), preference for dosing formulation (rimegepant: 16% vs. ubrogepant: 5%, lasmiditan: 9%; p < 0.05 – contrary to ubrogepant or lasmiditan, rimegepant was not studied to be potentially redosed within 24-hour of use (57,59).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations